2014
DOI: 10.4049/jimmunol.1301892
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β–Mediated Foxp3 Gene Expression Is Cooperatively Regulated by Stat5, Creb, and AP-1 through CNS2

Abstract: Foxp3 plays an important role in the development and the function of regulatory T cells (Treg). Both the induction and maintenance of Foxp3 gene expression are controlled by several regulatory regions including two enhancers in the conserved noncoding sequences (CNS). The functions of Enhancer 1 in CNS1 are well established, whereas those of Enhancer 2 in CNS2 remain unclear. Although CNS2 contains enhancer activity, methylated CpG sequences in this region prevent Foxp3 gene expression in Foxp3− T cells. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
79
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(86 citation statements)
references
References 43 publications
7
79
0
Order By: Relevance
“…However, an alternative tumour-specific signal to LP T reg generation during the process of tumorigenesis (which was not the purpose of this study) cannot be excluded. With reference to our observations, it has been proposed that, in different circumstances, TGF-b can generate T regs via diverse molecular pathways [dependent upon or independent of CD25 signalling] [32]. Furthermore, a previous study showed conversion of CD25 -T regs to CD25 1 T regs by TGF-b to mediate immunosuppression in tumours [33].…”
supporting
confidence: 65%
“…However, an alternative tumour-specific signal to LP T reg generation during the process of tumorigenesis (which was not the purpose of this study) cannot be excluded. With reference to our observations, it has been proposed that, in different circumstances, TGF-b can generate T regs via diverse molecular pathways [dependent upon or independent of CD25 signalling] [32]. Furthermore, a previous study showed conversion of CD25 -T regs to CD25 1 T regs by TGF-b to mediate immunosuppression in tumours [33].…”
supporting
confidence: 65%
“…Thus, IL-2 could be a factor that “positively” acts via CNS2 and whose deprivation leads to a pronounced loss of Foxp3 expression in the absence of CNS2 . Indeed, CNS2 contains multiple STAT5 binding motifs and can be bound by STAT5 (Figure S1A) (Ogawa et al, 2013; Yao et al, 2007). …”
Section: Resultsmentioning
confidence: 99%
“…14 DNA methylation experiments have revealed that the Foxp3 promoter and conserved non-coding DNA sequence 2 (CNS2) region are highly demethylated in tTregs, which facilitate mRNA transcription of Foxp3 and contribute to lineage stability through FOXP3 expression, while in vitro induced Treg cells are substantially methylated at the CNS2 region. 15,16 TGF-b treatment decreases the methylation status of CNS2 and promotes FOXP3 expression. Knockdown of the DNA methyltransferase Dnmt1 can also induce FOXP3 expression.…”
Section: Heterogeneity Of Treg Cellsmentioning
confidence: 99%